Global Incidence of Surgical Site Infection Among Patients: Systematic Review and Meta-Analysis - Dechasa Adare Mengistu MSc; Addisu Alemu MPH; Abdi Amin Abdukadir MD+; Ahmed Mohammed Husen MD+; Fila Ahmed MPH; Baredin Mohammed MPH; Ibsa Musa PhD (SAGE Publishing, 2023)
Healthcare-associated infections pose one of the most severe threats to patients' health and remain a major challenge for healthcare providers globally. Among healthcare-associated infections, surgical site infection is one of the most commonly reported infections. It remains a major cause of morbidity and mortality across the world. The aim of this study was to provide a pooled incidence of surgical site infection among patients on a regional and global scale. This study was conducted under the PRISMA guidelines developed for systematic review and meta-analysis. The studies were searched using electronic databases (SCOPUS, PubMed/MEDLINE, Web of Science, Google Scholar, DOAJ, and MedNar) from June 1st, 2022 to August 4th, 2022, using Boolean logic operators (AND, OR, and NOT), Medical Subject Headings (MeSH), and keywords. The quality of the study was assessed using the Joanna Briggs Institute Critical Assessment tool to determine the relevance of each included article to the study. A comprehensive meta-analysis version 3 was used to estimate the pooled prevalence of surgical site infections among the patients. A total of 2124 articles were retrieved from the included electronic databases. Finally, after applying inclusion criteria, 43 articles conducted in 39 countries were included in the current study. The global pooled incidence of SSI was found to be 2.5% (95% CI: 1.6, 3.7). Based on the subgroup analysis by WHO region and survey period, the incidence of SSI was 2.7% (95% CI: 2.2, 3.3%) and 2.5% (95% CI: 1.8, 3.5%), respectively. The highest incidence was reported in the African Region (7.2% [95% CI: 4.3, 11.8%]) and among studies conducted between 1996 and 2001 (2.9% [95% CI: 0.9%, 8.8%]). This study revealed that the overall pooled incidence of SSI was 2.5%. SSI estimates varied among the WHO regions of the world. However, the highest incidence (2.7%) was observed in the African region. This indicates that there is a need to implement safety measures, including interventions for SSI prevention to reduce SSI and improve patient safety.